The Effectiveness of Cognitive-Based Psychological Intervention on Compassion Fatigue: A Case Study of Female Teachers of Students with Autism Spectrum Disorder - Karimiha, Mohsen; Jenaabadi, Hossein; Alisofi, Allah Nazar (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to determine the effectiveness of cognitive-based therapy in reducing compassion fatigue among these teachers. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest format, a two-month follow-up period, and a control group. The statistical population consisted of all teachers working in autism schools in the city of Qazvin during the 2025–2026 academic year. From this population, 34 participants were selected using purposive sampling and were randomly assigned to either the experimental group (n = 17) or the control group (n = 17). The experimental group received cognitive-based therapy in 10 sessions, each lasting 90 minutes, whereas the control group received no intervention. Data were collected using the Compassion Fatigue Self-Test (CFST) developed by Figley and colleagues and were analyzed using repeated-measures analysis of variance in SPSS software, version 25. Findings: The results indicated that the cognitive-based intervention led to a significant reduction in compassion fatigue scores in the experimental group compared with the control group (p < .01). Repeated-measures analysis further demonstrated that this reduction remained stable at the follow-up assessment (p < .05). The effect size of the intervention for compassion fatigue was estimated to be large (η² = .48). Conclusion: By modifying cognitive biases and enhancing mental processing, cognitive-based therapy can serve as an effective intervention for reducing emotional exhaustion and promoting the mental health of teachers working in special education settings.